Commuication Abilities Crucial for Student Placemet (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Speech is dear as breath and is essential for employability. This paper (1) lists some of the factors responsible for poor communication skills of the students in engineering courses namely Learning a Technical Subject using a non-mother-tongue, Scope for practicing English speaking, A Non-Mother tongue generates uncomfortable vibrations in the body, A Non-Mother tongue affects the Breathing pattern, Lack of desire to master the English language, Lack of reading habit, Lack of tolerance, Fluctuating nature of Mind of the students, Lack of knowledge in Non-verbal or body language, Lack of Self-Control, Lack of knowledge of the technique of studying, Proficiency of Teachers of Technical Subjects in English and give solutions to some of these problems; (2) lists some of the factors in nonverbal communication the interviewers look for in a campus selection from the author’s view and suggests tips for improving performance in selection interviews, (3) to suggest a core course on meditation common to all engineering students to improve the learning skills namely listening, seeing, reading and speaking, and writing.